Comprensión de la construcción de las estrategias de afrontamiento de una cuidadora que asiste a una niña con osteogénesis imperfecta (2020)
Imperfect osteogenesis is a rare disease also called an orphan that is characterized by bones that break easily, literally it means bone that is imperfectly formed, this disease, due to its diagnosis, constitutes a great physical and psychological affectation in the patient and his family caregiver, since refers to the coping strategies assumed by care when living with the disease as various factors related to the quality of life of the affected patient.